Non-Nehari Manifold Method for Fractional p-Laplacian Equation with a Sign-Changing Nonlinearity - Huxiao Luo; Shengjun Li; Wenfeng He (Journal of Function Spaces)
We consider the following fractional p-Laplacian equation: -Δpαu+V(x)up-2u=f(x,u)-Γ(x)uq-2u,  x∈RN, where N≥2, pα⁎>q>p≥2, α∈(0,1), -Δpα is the fractional p-Laplacian, and Γ∈L∞(RN) and Γ(x)≥0 for a.e. x∈RN. f has the subcritical growth but higher than Γ(x)uq-2u; however, the nonlinearity f(x,u)-Γ(x)uq-2u may change sign. If V is coercive, we investigate the existence of ground state solutions for p-Laplacian equation.